Freedom of religion or belief as a pillar of sustainability: corporate social responsibility in the perspective of the Italian legislative decree 125/2024 and the 'Modena Charter' - Hussen, Basira (Il diritto ecclesiastico, 2025)
Summary · 1. eu Directive 2022/2464 and the Italian Legislative Decree 125/2024. 2. ‘Human rights’ and social sustainability in Legislative Decree 125/2024. 3. Freedom of religion or belief in Legislative Decree 125/2024. 4. The Modena Charter for respecting freedom of religion or belief in the workplace. 5. The inclusion of the Modena Charter in the 2025 Italian National Strategy for countering antisemitism